THE EFFECT OF PRICE, VARIATION PRODUCT AND SERVICE QUALITY ON BUYING DECISION AT MARKET PLACE SHOPEE - Miftahudin, Dwi; Sugiono, Sugiono; Rinnanik, Rinnanik; Desastra, Yolla Zelika; Buchori, Buchori (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to determine the influence of price, product variety and service quality on purchasing decisions at the Shopee market place at the As-Sya'roniyyah Islamic boarding school. This research method uses a quantitative approach. The population in this study was an unlimited number of students at the As-Sya'roniyyah Islamic boarding school. The sampling technique used Purposive Sampling Technique, with the criteria being that respondents had made purchases at the Shopee market place, at least twice, were at least 15 years old, male or female. Data collection techniques through distributing questionnaires to respondents who meet the criteria. The data analysis method used is Multiple Linear Analysis with SPSS (Statistical Product and Service Solution) version 25. This research proves that the more and higher the product variety and service quality, the more purchasing decisions will increase, while price is not able to increase purchasing decisions. There are many more variables that influence purchasing decisions that were not examined in this research. This research focuses on one object and the results of this research cannot be generalized to other objects that are not the same. Improving knowledge in making a strategy or decision in reaching potential consumers and retaining consumers in purchasing products in this research object This research focuses on the shopee market place object at the As-Sya'roniyyah Islamic boarding school with the variables price, product variety and service quality which are the variables that influence consumer purchasing decisions at that object. Keyword : price, product variation, quality service, buying decision